2015
DOI: 10.3168/jds.2015-9697
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dehydrogenase activity in Lactococcus chungangensis: Application in cream cheese to moderate alcohol uptake

Abstract: Many human gastrointestinal facultative anaerobic and aerobic bacteria possess alcohol dehydrogenase (ADH) activity and are therefore capable of oxidizing ethanol to acetaldehyde. However, the ADH activity of Lactococcus spp., except Lactococcus lactis ssp. lactis, has not been widely determined, though they play an important role as the starter for most cheesemaking technologies. Cheese is a functional food recognized as an aid to digestion. In the current study, the ADH activity of Lactococcus chungangensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In addition to genes that are useful for dairy products, L. chungangensis CAU 28 T also exhibits alcohol and aldehyde dehydrogenase activity, and reduces blood alcohol and aldehyde levels in mice (Konkit et al, 2015. However, the anti-AD, antiinflammatory, and antiallergy effect of L. chungangensis CAU 28 T has not been reported previously.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to genes that are useful for dairy products, L. chungangensis CAU 28 T also exhibits alcohol and aldehyde dehydrogenase activity, and reduces blood alcohol and aldehyde levels in mice (Konkit et al, 2015. However, the anti-AD, antiinflammatory, and antiallergy effect of L. chungangensis CAU 28 T has not been reported previously.…”
Section: Discussionmentioning
confidence: 94%
“…Previously, we have reported that this strain can be applied to the manufacture of dairy products and it has been found to possess functional activities such as alcohol dehydrogenase and aldehyde dehydrogenase, and other enzyme activities such as amylase, proteinase, and lipase (Konkit et al, 2014(Konkit et al, , 2015. However, the effect of L. chungangensis CAU 28 T on AD remains to be evaluated.…”
Section: Introductionmentioning
confidence: 96%
“…According to a published method used for making cream cheese (Konkit et al, 2015), pasteurized milk (Pasteur Milk Co. Ltd., Seoul, Korea) was heated at 68°C for 30 min and cooled down, 5% (vol/vol) of a starter Lactococcus strain was added, and the mixture was incubated at 30°C for 48 h. During this period, the milk was acidified. It was then stirred and heated at 70°C for 5 min, and subsequently the whey was separated through a cloth bag.…”
Section: Cream Cheese Makingmentioning
confidence: 99%
“…The LAB often play an important role in the starter cultures of commercial dairy prod-ucts, and ensure consistency of the process and product quality. Lactococcus is a genus of LAB that serves as a starter for several types of cheese, such as hard cheese without eyes or with small eyes (Leroy and De Vuyst, 2004), Cheddar (Cretenet et al, 2011), Moroccan soft white cheese (Ouadghiri et al, 2005), Domiati cheese (El-Baradei et al, 2007), and cream cheese (Konkit et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation